Malignant Hyperthermia in a 2-Year-Old Following General Anesthesia: A Rare Case Report from Nepal - Khadka, Bikash; Khanal, Kishor; Bhattarai, Prajjwal Raj; Khatiwada, Saurav; Poudel, Saroj; Tiwari, Prabal; Timalsina, Pratikshya; GC, Bijay (Nepal Mediciti Medical Journal, 2025)
Malignant hyperthermia (MH) is a pharmacogenetic disorder triggered by inhaled anesthetics or depolarizing muscle relaxants, leading to a catabolic state of skeletal muscle. Key clinical signs include tachycardia, hyperthermia, muscle rigidity, hypercapnia, acidosis, rhabdomyolysis, hyperkalemia, and renal failure. Without prompt and specific treatment, the mortality rate can reach 80%. However, early recognition and the administration of dantrolene sodium can reduce this rate to 5%. This article presents the case of a 2-year-old male patient admitted to the Intensive Care Unit with suspected MH following surgery for a crush injury to his left hand, which was performed under general anesthesia.